Valoración económica del aprovisionamiento de agua bosque de la comunidad Mocorita-Junín usando los métodos contingente y precio de mercado - Vélez Sabando, Luisa María (2017)
The aim of this research was to determine the value of water supply as an ecosystem service in the forests of the Mocorita-Junín area using the contingent valuation method and the market price method. A total population of 161 people was studied from a survey to 44 heads of household in the community. We used the Single Bound Logit model. The data were processed using R-project 3.2.0 and SPSS 21.0.0.0 to obtain the economic value in the contingent method. For the market price method, we used the m3 cost established by the local water company. The contingent method showed a yearly value of US $ 4128 that the community was committed to pay. This represents a monthly average of US $ 7.82 per household due to the difficulties and inconveniences with the water supply service already evident, and the commitment to preserve the forest for other ecological services that benefit the community. This is enough to ensure the survival of forest-bound ecosystems. The market price method showed a value of US $ 2472 according to the local water demand. Through the T test, we found a significant difference (p<0.05) between the economic value obtained with the contingent and market price methods. Therefore, the contingent valuation method presents a more consistent estimate of the water supply value of the La Mocorita forest.